Peran Motivasi dan Komunikasi dalam Pengaruh Efektivitas Kepemimpinan terhadap Perubahan Organisasi - Jeslyn, Jeslyn; Setyawan, Agustinus; Nelson, Alden (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze the relationship between leadership effectiveness and motivation and communication, and its influence on organizational change. Quantitative approach with PLS-SEM and questionnaires on 200 Batam manufacturing employees. The results showed that leadership effectiveness has a positive and significant effect on communication and motivation but not significant with organizational change. This study also proves that motivation and communication are able to mediate the influence between leadership effectiveness and organizational change.